Effect of mesohabitats on responses of invertebrate community structure in streams under different land uses - da Silva, Marcos Vinícius Dias; Rosa, Beatriz F. J. V.; Alves, Roberto G. (Environmental monitoring and assessment, 2015)
Riparian vegetation is one of the most important abiotic components determining the water flow pattern in lotic ecosystems, influencing the composition, richness, and diversity of invertebrates. We have identified whether differences in the structure of the assemblages of invertebrates between riffles and pools may influence the responses of fauna to the effects of land use. In addition, we investigated which fauna metrics are responsible for the differentiation between riffles and pools in streams subject to different land uses. During the dry season of 2012, the main substrates of riffles and pools were sampled (Surber collector) from nine streams within forest, pasture, and urban areas. Principal component analysis (PCA) and Permanova showed differences in the set of environmental variables between streams and mesohabitats. The first PCA axis distinguished the forest and pasture streams from the urban area streams and was related to variables indicative of nutrient enrichment and land use, while the second axis was formed by velocity flow and by the quantities of ultrafine and coarse sand, which distinguished the riffles and pools of the streams. The faunal composition distinguished the streams in pasture and forest areas from the urban streams. Riffles and pools were not concordant in the representation of the invertebrate fauna, indicating the importance of sampling both mesohabitats in the types of streams investigated. The richness, taxonomic composition, and relative abundance of families of Ephemeroptera, Plecoptera, and Trichoptera showed robust responses in riffles to the effects of environmental changes, while in pools, only the richness showed a significant response. It was possibly concluded that riffles were more sensitive in detecting the effects of land use. The information from this study help to understand how the community of invertebrates and the types of habitats in streams may be affected by anthropogenic impacts.